Lindane disturbs the capacity of Saccharomyces cerevisiae to scavenge lipid hydroperoxides via phospholipid hydroperoxide glutathione peroxidase causing cell death - Pita, T (2004)
Reactive oxygen species (ROS) are by-products of aerobic metabolism in cells. Pollutants such as lindane may raise its production, causing cell damages in biomolecules as lipids. Cells possess defence systems to counter oxidative stress including glutathione and glutathione peroxidases (GPx). Phospholipid hydroperoxide glutathione peroxidase (PHGPx) is considered to be the main line of enzymatic defence against membrane damage. The experimental advantages of the yeast model Saccharomyces cerevisiae have been exploited extensively for advancing our understanding aboutcell defences against ROS, because the yeast genome sequencing brevealed genes that encode GPx which exhibit great homology with other eukaryotes, including man. Lindane has been used as pesticide in agricultural and human health applications. Severalfactors have contributed in concern over the use of lindaneincluding its persistence, toxicity and bioaccumulation. Thus, the aim of this study was to evaluate the response to lindane medi ated by yeast GSH and PHGPx. Saccharomyces cerevisiae UE-ME3, a wild-type yeast deposited in the collection of laboratoryof Enology, University of Evora, at mid-exponential phase, were inoculated in YEPD medium, 2% (w/v) glucose, at 28°C, and shaken 150 rpm for 72 h in presence of 5 lM or 50 lM lindane and compared with control. Cell viability was determined by cfu and the biomass by dry weight. Yeasts harvested were suspended in 10 mM phosphate buffer pH 7.0 and disrupted by sonication. The post-12000 g pellets were used for determination of malondialdheyde (MDA), glutathione (GSH) and glutathione disulfide (GSSG) by fluorescence and the post-12000 g supernatant for PHGPx determination by spectrometry. Statistics were per-formed by ANOVA I and Duncan (p < 0.01) using SPSS for Windows, version 22. The results showed that lindane, at 72 h of exposure, inhibited yeast growth decreasing biomass produced and cell viability. On the other hand, it was observed, for both levels of exposition, an increase in the GSH/GSSG ratio and in the level of proteins, total glutathione, GSH, and MDA of mitochondria as well as a decrease in the PHGPx. The increase in GSH/GSSG ratio of mitochondria probably resulted from the incapacity of the cell to scavenge lipid hydroperoxides, via PHGPx, preventing cell damages in mitochondrial membranes.This effect may have determined an increase in the mitochondrial MDA content. This response probably contributed to slowdown the energetic metabolism and over express mitochondrial proteins. So, lindane was toxic to Saccharomyces cerevisiae UE-ME3, probably causing cell death by an active process.